A 6000-year record of surface-rupturing paleoearthquakes on the Wairau Fault, New Zealand. Issue 3 (3rd July 2018) - Nicol, Andrew; Dissen, Russ Van
ABSTRACT: The Wairau Fault is part of the Marlborough Fault System (MFS) in the northern South Island of New Zealand and is capable of generating future large-magnitude earthquakes. We use fault trenching and geomorphic mapping together with radiocarbon dating to constrain the timing, single-event displacement (SED), rupture length and magnitude of surface-rupturing earthquakes since 6000 yr BP. Data from two sites (Rainbow Station and Spring Creek) have been combined with published information to determine the timing of five large magnitude (e.g. M W  ≥ 7) paleoearthquakes at: 1750–970 (event 1), 2110–1930 (event 2), 3200–2700 (event 3), 4600–3950 (event 4) and 5600–4900 (event 5) yr BP. These earthquakes have a mean recurrence interval and SED of c. 1000 yr and 5.8 ± 2 m (1σ), respectively. The average recurrence interval for events 1–5 is less than the c. 2200 yr estimated for the long-term (c. 18 kyr) offshore record and suggests that onshore parts of the fault could have experienced a period of increased earthquake frequency since 5600 yr BP. These five surface-rupturing earthquakes had rupture lengths of ≥ 6 to 140 km and moment magnitudes of at least M W 7–7.7. Co-rupture of the Wairau and Alpine faults during great earthquakes occurs rarely (if at all) on millennial or longer timescales.